Production and contamination of pasteurized beverages packed in sealed plastic containers in Thailand and potential preventive measures - Chavasit V. (2014)
From 35 premises that were sampled in this study, 86%, 69%, 59%, and 13% of pasteurized beverages packed in sealed plastic containers were contaminated with yeast, mold, coliform, or E. coli, respectively. The products could be divided into two groups, i.e., heat sensitive and non-heat sensitive. At least 45% of the premises did not pass the Thai Food and Drug Administration (FDA) requirements for GMP. Chlorine treatment and temperature control were needed for heat sensitive products. Appropriate equipment and methods for double boiling, cooling, washing containers, and sanitizing utensils were developed. The developed systems were found to be feasible in four tested premises. © 2005 Elsevier Ltd. All rights reserved.